Didactic strategies to strengthen chemical language in education - Flores Hinostroza, Elizeth Mayrene; Mendoza Velazco, Derling Jose; Soledad Revilla, Lorena; Castillo Pinos, Karina Maribel (Indonesian Institute for Counseling, Education and Theraphy, 2022)
The objective of the research article presented below was to propose activities that would strengthen the students of the educational institution